Editorial Introduction: Prioritizing the Future, Collaborating in the Present, and Archiving the Past - Timothy M. McGeary (Code4Lib Journal, 2011)
This is an exciting time for libraries and technology, and libraries have the opportunity now to build strong collaborations that both preserves our rich history and prioritizes our future. This issue shines a light on a unique blending of priorities old and new, detailed analysis of our past, and creative solutions that enhance the mission of libraries. Libraries big and small have the chance to impact our communities for the better. Come along, it's going to be a great ride.